Isolation, cloning and sequence analysis of gene encoding the lactate dehydrogenase enzyme from Theileria parva - Icen, I.; Celik, V.; Pelle, R.; Aytan, E.; Munzuroglu, O.; Geckil, H. (Wiley-Blackwell, 2011)
[Abstract Not Available]
36th FEBS Congress of the Biochemistry for Tomorrows Medicine -- JUN 25-30, 2011 -- Torino, ITALY
Keywords: Theileria parva; tick-borne disease; antitheilerial; lactate dehydrogenase; insertion